ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ANGGARAN PENDIDIKAN DI INDONESIA TAHUN 2015-2021 - Atu Bagus Wiguna; Muhammad, Pramanda Rafi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The role of the government is indispensable in implementing education development through government spending. Government spending can be reflected as a description of the plan chosen by the government in an area. The Indonesian government annually allocates an education budget from the APBN and APBD of at least 20% to create a quality education system. The World Bank still finds inequality in the unequal distribution of allocations per student Another condition is the transfer of physical DAK that does not match the required infrastructure. Similarly , it was also found that there are variations in education spending and performance between regions, inefficient spending, the contribution of education spending from PAD that is decreasing, and the need for synergy between spending this research aims to determine the influence of several factors on the education budget in Indonesia in 2015-2021. This research is a quantitative research with its data analysis method, namely panel data regression analysis. The results showed that teacher qualifications do not affect the education budget. Meanwhile, the Human Development Index and the Number of Students can affect the education budget .